2019
DOI: 10.2533/chimia.2019.277
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Polymeric Solids by Supramolecular Means

Abstract: Equipping a polymeric material with the ability to heal an inflicted damage is a crucial advantage for many applications. The incorporation of reversible and dynamic supramolecular interactions into polymeric systems has proven to be a promising route towards such materials. In this article, recent developments in the field of healable materials are highlighted with a particular focus on the design principles, driving forces, and mechanisms that allow healing to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In addition to the nature of the binding motifs and the usually telechelic polymer core employed to connect them into (macro)­monomers, effects such as the aggregation, phase separation, glass formation, or crystallization of the binding motifs or the telechelic core significantly influence the properties of supramolecular polymers in the solid state, particularly by restricting the molecular mobility in the system. The formation of lamellar morphologies has been reported for several MSPs, including materials made by assembling 2,6-bis­(1′-methyl­benzimidazolyl)­pyridine (Mebip) end-capped telechelic penta­(ethylene glycol) or poly­(tetrahydrofuran) macromonomers with Zn­(ClO 4 ) 2 , Mebip-terminated poly­(ethylene- co -butylene) with Zn­(NTf 2 ) 2 or La­(NTf 2 ) 2 , and Mebip-terminated poly­(tetrahydrofuran) with mixtures of Zn­(ClO 4 ) 2 and Eu­(ClO 4 ) 3 . In all of these materials, crystalline or glassy (solid amorphous) hard domains formed by the binding motifs act as physical cross-links at ambient temperatures, while the telechelic cores form a low-glass-transition soft phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the nature of the binding motifs and the usually telechelic polymer core employed to connect them into (macro)­monomers, effects such as the aggregation, phase separation, glass formation, or crystallization of the binding motifs or the telechelic core significantly influence the properties of supramolecular polymers in the solid state, particularly by restricting the molecular mobility in the system. The formation of lamellar morphologies has been reported for several MSPs, including materials made by assembling 2,6-bis­(1′-methyl­benzimidazolyl)­pyridine (Mebip) end-capped telechelic penta­(ethylene glycol) or poly­(tetrahydrofuran) macromonomers with Zn­(ClO 4 ) 2 , Mebip-terminated poly­(ethylene- co -butylene) with Zn­(NTf 2 ) 2 or La­(NTf 2 ) 2 , and Mebip-terminated poly­(tetrahydrofuran) with mixtures of Zn­(ClO 4 ) 2 and Eu­(ClO 4 ) 3 . In all of these materials, crystalline or glassy (solid amorphous) hard domains formed by the binding motifs act as physical cross-links at ambient temperatures, while the telechelic cores form a low-glass-transition soft phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the factors influencing the properties of metallosupramolecular elastomers have their unique complexity. Studies on supramolecular elastomers have shown that the overall performance of the materials depends more on the kinetic properties rather than the association constants of the supramolecular interactions. In addition, the properties of solid supramolecular elastomers are also significantly affected by microscopic structures such as network morphology, aggregation, phase separation, and crystallization. …”
Section: Introductionmentioning
confidence: 99%
“…For example, directional noncovalent interactions such as hydrogen bonds, π-attractive forces, and metal-ligand interactions generally respond to external stimuli in a reversible manner. [32][33][34][35][36] When employed in polymers, the motifs can not only provide nonsacrificial pathways for the dissipation of energy in response to mechanical deformation, but also endow the host material with a plethora of other properties and functions such as healing capabilities, [33,[35][36][37] enhanced toughness, [38] and improved melt-processing characteristics. [32,39] Furthermore, noncovalent binding motifs can be designed to feature a very wide range of interaction strengths, with association constants (K a ) varying from relatively low values of ≈10 2 M −1 for, e.g., double hydrogen-bonding motifs, up to very high association constants of ≈10 14 M −1 for the interaction in complexes of tridentate ligands and metal-ions.…”
Section: Introductionmentioning
confidence: 99%